STUDENTS’ PERCEPTION ON THE USE OF HOT POTATOES IN ENGLISH SUBJECT: A Descriptive Qualitative Research - Askin, Amelia; Akib, Erwin; Azis, Awalia (FKIP Unismuh Makassar, 2018)
This research was aimed at revealing students’ perceptions on the use of hot potatoes in English subject at the 5th semester students of English Education department at Makassar Muhammadiyah University. This research applied descriptive method that spending one month period of time for the data collection by using questionnaire as well as focus group discussion consisting 8 statements to be analyzed. The data was taken from 15 students by using purposive sampling technique of the 5th semester students of English Education department in order to find out students’ perception on the use of hot potatoes in English subject. The result of data analysis revealed that all participants had positive perception toward hot potatoes. The first variable revealed students’ perception on the use of hot potatoes where the average participants clarified that the program was suitable for language testing. The second variable revealed students’ perception on the teacher strategy in teaching English by using hot potatoes. With the regard of this program, participants clarified that was an appropriate strategy for English evaluation. Based on the result above, it can be concluded that according to students’ perception, hot potatoes was user friendly program and appropriate strategy for English subject